Discovering Autism Child Potential using Autism Parenting Application - Aslina Baharum; Sakinah Ali Pitchay; Rozita Ismail; Emelia Abdul Rahim; Suhaida Halmy; A. Bhanupriya Naidu a/p Anathan (2019)
Autism have become prevalent disorder among children nowadays. Parents with autism kid having higher level of stress among other parents. There is some remarkable skill in autism kid that by discovering the skill can make parents to have a better approach or better parenting toward their kid. The objective of the study is to identify the remarkable skills among autism children using qualitative method and to identify the features of suitable mobile app to help parent determine the remarkable skills using content analysis and literature review. Two main remarkable skill focusses in this study were rote memory and spatial visual. A study was carried out to produce a mobile application (prototype) for autism parents to discover their child’s remarkable skills. Prototyping methodology was employed. The application is expected to help parents to discover their kid’s remarkable skill. Index Terms - Autism, parenting application, remarkable skill, rote memory, spatial visual.